2014
DOI: 10.1371/journal.pone.0113648
|View full text |Cite
|
Sign up to set email alerts
|

Species, Habitats, Society: An Evaluation of Research Supporting EU's Natura 2000 Network

Abstract: The Natura 2000 network is regarded as one of the conservation success stories in the global effort to protect biodiversity. However, significant challenges remain in Natura 2000 implementation, owing to its rapid expansion, and lack of a coherent vision for its future. Scientific research is critical for identifying conservation priorities, setting management goals, and reconciling biodiversity protection and society in the complex political European landscape. Thus, there is an urgent need for a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 60 publications
4
72
0
3
Order By: Relevance
“…Species richness and management are among the most important issues of the scientific research supporting EU's Natura 2000 network (Popescu et al 2014). Nonetheless, studies focusing on the direct ef-321 iForest 9: 318-324 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Species richness and management are among the most important issues of the scientific research supporting EU's Natura 2000 network (Popescu et al 2014). Nonetheless, studies focusing on the direct ef-321 iForest 9: 318-324 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This might be an indication that the processes that have been initiated by the different governments to adapt the management of the sites in the reviewed areas is starting to have an effect on the actual management of the sites. Existing Natura 2000 literature until now has not provided any information on other studies assessing this aspect of Natura 2000 implementation (Popescu et al 2014). Interestingly enough this opinion does not depend on the respondents actor type.…”
Section: Discussion Of Resultsmentioning
confidence: 94%
“…Overall limited research -whether ecological, sociological or economic has been undertaken to evaluate the implementation of the Birds and Habitats Directive (Popescu et al 2014). Evaluation research on the impact of the Natura 2000 policy at site level is therefore needed, whether quantitate or qualitative and preferable an evaluation that uses criteria that review ecological, economic and social aspects of implementation.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…First, the social network metric modularity class (Blondel et al 2008;Newman 2006) identified components that are more connected to each other than others, thus representing big thematic fields or research hotspots in a more detailed way than the original WoS categories. Second, degree centrality was calculated to measure the number of relations between categories and keywords (see Popescu et al 2014). A node with high degree centrality has many connections in the network and connects papers with similar ideas or approaches.…”
Section: Geographic Distribution and Collaborationsmentioning
confidence: 99%